Experimental analysis of rainfall-induced shallow landslides: a case study of a loess slope in Gaolan County, China - Liu, Jinwen; Shen, Zhaolong; Hu, Bowen; Zhang, Yongjun; Ou, Xiao; Cong, Kai; Bi, Yuanhong; Li, Yanan; Dai, Baofeng; Liu, Ping (Frontiers in Earth Science, 2025)
Rainfall is a major trigger for loess landslides, and understanding the associated deformation and failure mechanisms is essential for effective hazard mitigation. This study employed physical model experiments to investigate the hydrological response, deformation behavior, and failure evolution of homogeneous loess slopes subjected to intermittent rainfall. Key parameters, including volumetric water content, pore water pressure, wetting front migration, and displacement, were continuously monitored throughout the tests. The results revealed periodic fluctuations in hydrological parameters and spatially heterogeneous responses across the slope. Repeated transitions between saturated and unsaturated conditions, combined with surface runoff erosion and seepage-induced forces, contributed to a progressive reduction in soil shear strength and increased slope instability. The failure process evolved through three distinct stages: toe erosion, fissure expansion, and gully erosion. These findings improve the understanding of rainfall-induced loess slope failures and support the development of stage-specific hazard mitigation strategies.